Controlled growth of anodic aluminium oxide films with hexagonal array of nanometer-sized pores filled with textured copper nanowires - Bertholdo, R. [UNESP]; Assis, M. C. [UNESP]; Hammer, R. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier B.V., 2010)
Anodic aluminium oxide (AAO) films exhibiting a homogeneous morphology of parallel pores perpendicular to the surface were prepared in a two-step anodization process and filled with copper by electrochemical deposition. The optimum growth conditions for the formation of freestanding AAO films with hexagonal compact array of cylindrical pores were studied by field emission scanning electron microscopy and small angle X-ray scattering. The results show well-defined periodic structures with uniform pores size distribution for films with pore diameters between 40 and 70 nm prepared using different voltages and temperatures during the second anodization step. X-ray photoelectron spectroscopy and X-ray diffraction analysis of AAO films filled with copper show the formation of nanowires with high structural order, exhibiting a preferential crystalline orientation along the (2 2 0) axis and only small fraction of copper oxides. The best results for textured Cu nanowires were obtained at a reduction potential of -300 mV. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Anodic alumina films; Self-organized pore arrays; Copper nanowires; Structural properties